Impact of Intracystic Hemorrhage on Therapeutic Outcomes in Macro/Mixed Cystic Lymphatic Malformation: A Retrospective Cohort Study - Tao Han; Daolin Ye; Jie Cui; Songming Huang; Weimin Shen (Children)
Objectives: This research aims to examine the impact of intracystic hemorrhage (ICH) on therapeutic outcomes in children with macro or mixed cystic lymphatic malformation (cLM). Methods: This retrospective study included macro/mixed cLM cases with or without ICH who underwent treatment between January 2019 and June 2024. All patients were diagnosed using preoperative imaging findings and intraoperative indocyanine green (ICG) lymphography. The baseline data of enrolled cases were retrospectively collected. The clinical characteristics were documented, including gender, age, histological typing, location, maximum diameter, and intracystic condition. Patients with or without ICH were divided into two groups. The dependent variables for predicting an excellent outcome were analyzed using multivariable logistic regression models after adjusting for potential factors using a univariable regression model. Postoperative variables, including duration of negative drainage, local infection, scar hyperplasia, and follow-up, were compared between the two groups. Results: A total of 83 cLM patients were included (ICH group: n = 36 and without ICH group: n = 47). A complete absence of afferent lymphatic vessels was demonstrated using intraoperative ICG lymphography, suggesting the isolated nature of ICH cases. ICH (p = 031; OR, 2.560; 95% CI, 1.089–6.020) was identified as the main predictor, and younger patients (p = 035; OR, 0.415; 95% CI, 0.183–0.940) had a lower potential for excellent outcomes. For the postoperative variables, the ICH group exhibited a shorter duration of negative drainage than the without ICH group (p < 0.001), while no significant differences were found regarding local infection (p = 0.693) and scar hypertrophy (p = 0.648). Conclusions: Although characterized by aggressive progression and compressive symptoms, ICH emerges as an independent favorable prognostic predictor in macro/mixed cLM management, potentially attributable to its isolated nature.